2017
DOI: 10.1002/chem.201604654
|View full text |Cite
|
Sign up to set email alerts
|

New Conjugated meso‐Tetrafluorenylporphyrin‐Cored Derivatives as Fluorescent Two‐Photon Photosensitizers for Singlet Oxygen Generation

Abstract: A series of three conjugated meso-porphyrin dendrimers containing conjugated dendrons featuring 2,7-fluorenyl groups, incorporating overall 8, 12, or 28 fluorenyl units have been synthesized and characterized. The photophysical properties of these new compounds were studied in the context of photodynamic therapy. The relevant linear and nonlinear optical properties were measured in organic media and useful structure-properties relationships were derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 75 publications
2
51
0
Order By: Relevance
“…For these dendrimers, the 2,7-fluorenyl arms were connected directly to the meso positions of the central porphyrin core (i.e., featuring TFP core). Interestingly, in these assemblies, the conjugated peripheral arms incorporate fluorene units at both terminal and internal positions [26]. We also observed that the various fluorene-containing dendrons act as light-harvesting antennae, before transferring their energy to the central porphyrin core.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…For these dendrimers, the 2,7-fluorenyl arms were connected directly to the meso positions of the central porphyrin core (i.e., featuring TFP core). Interestingly, in these assemblies, the conjugated peripheral arms incorporate fluorene units at both terminal and internal positions [26]. We also observed that the various fluorene-containing dendrons act as light-harvesting antennae, before transferring their energy to the central porphyrin core.…”
mentioning
confidence: 66%
“…We also observed that the various fluorene-containing dendrons act as light-harvesting antennae, before transferring their energy to the central porphyrin core. Although the emission quantum yields are slightly diminished compared to that for the smaller TFP reference compound [20], we showed that their brightness was much improved [26].…”
mentioning
confidence: 70%
See 3 more Smart Citations